Efektivitas Program Bantuan Sosial Non Tunai (BPNT dan PKH) di Kota Mojokerto - Nurofik, Ichwan; Kolopaking, Lala M. (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 10 No 1 (2022): Jurnal Manajemen Agribisnis, 2022)
This research aims to analyze the effectiveness of the BPNT (Sembako) program in Mojokerto City from the 7R aspect (right target, purpose, quantity, price, quality, time and administration) and PKH from the 5R aspect (right target, quantity, purpose, time and administration). Primary and secondary data used in this research were collected from field observations, in-depth interviews and documentation studies. While the Interactive Model (Miles et al. 2019) was used for data analysis. The results of the research provided an overview of the implementation of the BPNT (Sembako) program in Mojokerto City that has been carried out effectively indicated by the 7R (right target, objective, quantity, price, quality, time and administration) as well as contributing to financial inclusion. Right target was indicated by the fact that all KPMs have been included in the DTKS. Right time and administration were indicated by the distribution of assistance carried out regularly every month. While right objective, price, quantity and quality were indicated based on the commodities provided by e-Warong for KPM to buy. The effectiveness of PKH was indicated on the 5R (right target, goal, quantity, time, and administration). Right target was indicated by all KPMs that have been included in the DTKS, Right time and administration were indicated by the distribution of assistance carried out routinely 4 (four) times a year, Right quantity indicated by the amount of money received by the KPM could be seen on ATMs or printed savings books.